Aerobic exercise preconditioning suppresses subcutaneous tumorigenesis via PI3K/AKT-driven metabolic epigenetic reprogramming and immune microenvironment remodeling - Xue Zhang; Yixue Xia; Lingbing Zheng; Lu Cao; Zhengtang Qi; Shuzhe Ding (Experimental Gerontology)
It has been widely recognized that aerobic exercise inhibits tumors, and aerobic glycolysis is closely related to tumor development. Whether exercise preconditioning inhibits subcutaneous tumor growth remains unclear. This study aimed to investigate the effect of aerobic exercise preconditioning on subcutaneous tumors in tumor-bearing mice and determine its mechanism. We first subjected the mice to aerobic exercise for 12 weeks, followed by the subcutaneous transplantation of Hepa1–6 cells under the right armpit. Compared with the control group, aerobic preconditioning significantly inhibited Hepa1–6 tumor growth and reduced the expression of PKM2, GLUT1, LDHA, and HK2 in tumor tissues. RNA-Seq showed that differentiated gene expression in the aerobic exercise group was enriched in the PI3K/AKT signaling pathway. Western blot detection showed that P-PI3K and P-AKT proteins were significantly downregulated in the tumor tissue of the exercise group. Meanwhile, RNA-Seq showed that exercise downregulated the expression of genes related to glucose metabolism. The TISCH2 database single cell population gene cluster map (macrophage population) suggested that these genes were closely related to immune cell infiltration. Immunofluorescence assay also showed that exercise significantly reduced the inflammatory infiltration of M1 macrophages. Moreover, in mice with DEN-induced HCC, the anticancer effects of aerobic exercise were related to liver DNA methylation, and the differential methylation sites were enriched in the PI3K/Akt pathway. Therefore, the antitumor effect of exercise intervention is directly related to the epigenetic reprogramming of tumor metabolism, suggesting that the PI3K/AKT pathway is the central component in the exercise regulation of tumor metabolism.